Institutional quality management and organizational development of educational institutions - Godoy-Tucto, Eloidit (2019)
The present investigation arose as having poor corporate governance problem that materialized in educational institutions at primary education Yarowilca Province , the methodology, experimental synchronous or sectional level macroeducativo developed was used in addition research is related to discipline, because the research problem is associated with the application of theoretical and practical foundations of Institutional Quality Management (discipline) in Organizational Development of educational institutions at primary education in the province of Yarowilca. The results show that there is a significant difference between the statisticians of central tendency and dispersion corresponding to the pre-test to post-test in the experimental group, thereby demonstrating that the institutional quality management has a definite impact on improving the organizational climate educational institutions from primary level Yarowilca province.